Cytokeratin immunoprofile of primary and metastatic adenoid cystic carcinoma of salivary glands: a report of two cases - Cibele Pidorodeski Nagano; Cláudia Malheiros Coutinho-Camillo; Clovis Antônio Pinto; Fernando Augusto Soares; Filipa Santos; Isabel Fonseca; Silvia Vanessa Lourenço (University of São Paulo, 2016)
Distant metastases from salivary gland tumors are considered infrequent: the incidence of distant metastases ranges from 24% to 61% according to different histotypes and to the site of the primary mass. The most common site of distant metastases due to salivary gland malignancies is the lung. From the pathology point of view, cytokeratins (CK) are important differentiation markers in salivary gland tumors, which are often used for the diagnostic process. Their employment also may be useful to identify and confirm the diagnosis of their distant metastases. We report the expression of CK in two cases of primary and metastatic adenoid cystic carcinoma (ACC) and their CK profiles of the primary and metastatic masses. Both patients-one male and one female-were diagnosed with an ACC cribriform and tubular, respectively, with lung metastases. In case 1, the metastatic mass presented the same histotype and CK profile of the primary tumor. For case 2, the metastatic lung mass was distinct from the primary mass (a solid ACC) and presented a different CK profile. Although salivary gland metastatic disease presents a poor prognosis, both patients reported herein are alive despite the presence of the disease in long-term follow-up. Therefore, the modifications seen in the CK profiles do not appear to be predictive of tumor behavior and outcome. The use of a CK profile seems to be useful to identify the nature of a distant mass and its possible correlations with a primary salivary gland tumor